STRATEGI KEPALA SEKOLAH DALAM PEMBENTUKAN AKHLAQUL KARIMAH PESERTA DIDIK BERBASIS WISATA EDUKASI DI SMP BAHRUL MAGHFIROH MALANG - Ahmad Labib Abdi Pangestu; Dwi Fitri Wiyono; Indhra Musthofa (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The principal's leadership is very influential on the rate of development of the institution he leads. Including a harmonious learning environment is also inseparable from the influence of the principal who creates a comfortable and disciplined school culture for teachers, education staff and especially for students. SMP Bahrul Maghfiroh Malang is a pesantren-based institution that has a unique school theme, namely the theme of an educational tourism school. The focus of this research is to describe the akhlaqul karimah attitude of students, describe the principal's strategy in the formation of akhlaqul karimah in students based on educational tourism, and describe the obstacles and solutions in the process of forming akhlaqul karimah. This research uses a qualitative approach with the type of case study research. The researcher found that the description of the students' akhlaqul karimah attitude covered the scope of morality. on the principal's strategy includes programs and engagement. as well as obstacles and solutions for handling students' moral attitudes.